Clima e devoção na Terra de Miranda durante a Idade Moderna - Mourinho, António Rodrigues (Trabalhos de Antropologia e Etnologia, 2020)
The «plateau» where Miranda do Douro stands (the «Planalto Mirandês») has been affected, as well as the whole province of Trás-os-Montes, by the typical sharp changes of weather in the region: freezing cold in winter and burning hot in summer. There are years when rain does not stop from mid September to the end of November, or perhaps December, preventing the sowing of the fields from being dane in due time. In the same way, springtime can also be too wet, or too dry, with an adverse effect on the harvest of grain. The inhabitants of the «plateau», as well as the people of the whole region, are known to have been religious ali through the various eras known to us, i.e. from pre-historical to our times. Rituais and festivities of pagan origin are still being performed today by the locais. As the economy of these people depends entirely from the proceeds of thé land, they get into panic when faced with a severe year, that is to say: hunger and calamity. Thus, their only refuge during bad agricultura! years is the believe in supernatural powers. The length of their believe is affirmed by the many shrines and images of Saints still existing in Miranda. There are also many documents, written from 1594 up to the beginning of the XIX century, which testify the devotion and worship of «Santo Cristo da Misericórdia». The image of this Saint, dating from the XV century, is still being worshipped today anel can be seen at the parish church of Miranda do Douro.